The global landscape of digital determinants of FDI: A bibliometric analysis of the transition to digitalization and artificial intelligence - Mohd Ishak@Zainudin, Fadhilah; Idris, Asma’ Rashidah; Wan Mustapha, Wan Masnieza; Shari, Asma Shazwani; Mustafa, Tismazammi (International Journal of Accounting, Finance and Business, 2026)
The connection of digital transformation and international capital flow has appeared as a critical focus of modern macroeconomic debate. Understanding the determinants that attract foreign direct investment (FDI) has become a primary policy agenda for nations seeking to bridge the digital boundaries and foster sustainable growth. Thus, this study offers a comprehensive bibliometric analysis of scholarly literature by exploring the digital drivers of FDI. Hence, the analysis map out 222 documents, extracted from the Scopus database spanning from 1999 to 2026. The bibliometric analysis was carried out through Biblioshiny software (via the R-package Bibliometrix) to analyses the structural and conceptual evolution of the field. The performance parameters demonstrate a significant growth in annual publication volumes and citation impacts. This shows that the research field has reached a global concern from academic scholars. The geographical analysis found that China has been the pioneer leader followed by United States, India, Saudi Arabia, Malaysia and Romania. Thematic network mapping portrays that the publication has progressed from basic ICT infrastructure, shifting towards innovation, digital governance, and environmental sustainability converge. Hence, this study contributes the research sphere by transforming a dispersed global data into a structured overview to facilitate the future research direction.